Genome and drug resistance analysis of Mycobacterium abscessus complex on tropical islands in China - Wang, Jieying; Li, Chunrong; Zheng, Xianliang; Chen, Zhuolin; Ye, Wen; Xu, Yuni; Qiu, Wenhua; Chen, Shaowen; Pei, Hua; Zhong, Yeteng (Frontiers in Microbiology, 2026)
ObjectiveBased on whole-genome sequencing (WGS) technology, the species distribution, genetic correlations, virulence and drug resistance gene characteristics of the clinical isolates of Mycobacterium abscessus complex (MABC) in the tropical island of China (Hainan) were analyzed to provide a basis for clinical precise diagnosis and treatment.MethodsA total of 113 MABC strains from the Second Affiliated Hospital of Hainan Medical University from 2014 to 2023 were collected. Whole-genome sequencing (WGS) was used for subspecies identification (Average Nucleotide Identity, ANI), genetic distance analysis (single nucleotide polymorphism, SNP), and pan-genome analysis. The distribution of virulence and antibiotic resistance genes was analyzed through the Virulence Factor Database (VFDB) and the Comprehensive Antibiotic Resistance Database (CARD). The drug susceptibility phenotypes were detected by the microbroth dilution method.ResultsAmong the 113 MABC strains, M. abscessus subsp. abscessus (Mab) accounted for 65.5%, M. abscessus subsp. massiliense (Mma) accounted for 33.6%, and M. abscessus subsp. bolletii (Mbo) accounted for 0.9%. The strains showed high genetic diversity among them, but two pairs of Mab strains with high genetic similarity (differing by 5 and 8 SNPs respectively) were identified, suggesting the possibility of local common exposure. The pan-genome is open-ended and consists of 3,626 core genes and highly variable accessory/unique genes. The virulence genes show species-specific differences: the detection rate of the phenolic lipid synthesis gene papA5 in Mma is significantly higher than that in Mab (92.1% vs. 47.3%, p < 0.001), while the PDIM synthesis gene ppsE is significantly lower in Mma (0.0% vs. 98.6%, p < 0.001). The drug sensitivity test shows that the 14-day induction of resistance rate of Mma to clarithromycin is significantly lower than that of Mab (5.3% vs. 86.5%, p < 0.001). Resistance genes are widely carried, including rrs a1408g (99.1%), rrl a2059g (98.2%) mutations, and the efflux pump gene qacJ in Mma (97.4%).ConclusionIn Hainan region, environmental exposure is the main source of MABC infection. Whole genome analysis suggests the potential risk of local common exposure. Mma has a better treatment prospect due to its low clindamycin resistance rate. The differentiation of virulence and resistance genes among subtypes provides a molecular basis for the precise prevention and control of MABC infection in tropical regions.